Implementing asset-based community development : a case study from the Philippines : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Anna, Bona (Massey University, 2005)
Within the alternative development paradigm, needs-based models have been critiqued for the part they play in accentuating local deficiency and thereby increasing dependency on externally-driven development. The asset-based approach to community development (ABCD) has been presented as a capacities-focused alternative, aimed at establishing community-driven development and promoting authentic local empowerment. This thesis presents a case study into ABCD as it has been applied in a developing country context, analysing it in relationship to some of the theoretical premises of the approach and the wider development literature. The research, undertaken on the island of Mindanao in the Philippines, describes how the ABCD model was implemented and adapted to local circumstances. The findings indicate that the ABCD intervention resulted in improvements within the case study community, particularly pertaining to the expansion of community facilities, livelihood choices, household incomes, individual and collective motivation, and community pride. Overall, this study endorses ABCD as an effective approach to development in the developing world, while at the same time highlighting issues associated with its implementation. Questions are also raised regarding three global development themes that emerged in the course of the study, namely the development of capacity, the management of social process and the meaning of empowerment.
Keywords: Philippines; Community development; Citizen participation; Rural development; Mindanao Island -- Midkiwan -- Case studies